Immobilization of lead (Pb) using ladle furnace slag and carbon dioxide - Xu, Bo (2022)
Global sustainable development faces challenges in greenhouse gas emissions, consumption of energy and non-renewable resources, environmental pollution, and waste landfilling. Current technologies for immobilization of heavy metals face similar challenges; for example, the use of cement, magnesia, lime, and other binders for immobilization of heavy metals is associated with carbon dioxide emission and consumption of limestone/magnesite and energy. In these contexts, this study introduced a novel and sustainable method for immobilization of lead (Pb) by using an industrial solid waste (ladle furnace slag, LFS) and a greenhouse gas (carbon dioxide). In this laboratory investigation, LFS was first mixed with the lead nitrate and then treated by conventional curing (without carbon dioxide) and carbonation curing (with carbon dioxide) for different periods. The treated LFS were then analyzed by various chemical analyses and microanalysis. The results showed that LFS with conventional curing is not effective in immobilization of lead, while LFS with carbonation curing can effectively immobilize lead. The leaching concentrations of Pb from carbonated LFS were four orders of magnitude lower than those with conventional curing. LFS can achieve carbon dioxide uptake of up to 8% of LFS mass. During the carbonation process, carbonates were produced and wrapped LFS particles to prevent the release of lead, lead nitrate was also carbonated into lead carbonate, and the pH of LFS was reduced to 9.36-9.58, close to the minimum solubility of lead carbonate; these are the main reasons for lead immobilization. In summary, the use of LFS with carbon dioxide for immobilization of lead can not only sequester carbon dioxide, but also reduce the cost of binders, non-renewable resource consumption, energy use, and LFS landfilling.